Changing Family Structure and Development of Self and Values: The Impact of Changing Family Structures on Self and Values (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Family life and family ideals have changed dramatically in the past generation. The very natureof the family unit itself has changed, and with it, the values and attitudes surrounding it. There is lessemphasis on marriage and more cohabitation, family size and stability have decreased, attitudes towardchildren and parenting have shifted, and conventional gender roles within marriage have shifted fromhierarchical to more egalitarian. Two hundred youngsters between the ages of nine and twelve made upthe sample. There was a 5050 split between rural and urban residents in the Allahabad district, and theresults of the regression analysis revealed the degree to which the predictor factors strongly predictedthe different criterion variables. Changes as a whole represent a shift away from conventional familystructures and norms in favor of more nonconformist, progressive models.